Clinical implications of JUPITER in a United States population: insights from the Atherosclerosis Risk in Communities (ARIC) Study - Yang, Eric Y. (2009)
OBJECTIVES: To describe the proportion of “JUPITER-eligible” individuals and clinical outcomes of individuals based on high-sensitivity C-reactive protein (hs-CRP) and low-density lipoprotein cholesterol (LDL-C) strata in the Atherosclerosis Risk in Communities (ARIC) study. BACKGROUND: Questions remain after the JUPITER study including whether the observed cardiovascular disease (CVD) event rates would persist with time and how these event rates would compare with other populations (lower hs-CRP and/or higher LDL-C levels). METHODS: After stratification into 4 groups based on LDL-C and hs-CRP levels, with cutoffs at 130 mg/dL and 2.0 mg/L, respectively incident CVD events were examined (mean follow-up 6.9 years) and compared. RESULTS: Of 8,907 age-eligible participants, 18.2% (n=1,621) were “JUPITER-eligible” (hs-CRP ≥2.0 mg/L, LDL-C <130 mg/dL) and had an absolute CVD risk of ~10.9% over a mean follow-up of 6.9 years (1.57% per year). If JUPITER hazard ratios were applied to this group, the number needed to treat to prevent one CVD event would be estimated at 38 over 5 years and 26 over 6.9 years. CONCLUSION: ARIC participants with elevated hs-CRP and low LDL-C had a CVD event rate of 1.57% per year over 6.9 years similar to the CVD event rate noted in the JUPITER study placebo group (1.36% per year over 1.9 years). The association of hs-CRP ≥2.0 mg/L with increased CVD risk and mortality regardless of LDL-C provides us a simple method of using age and hs-CRP for identifying higher risk individuals.